2019
DOI: 10.1002/nme.6204
|View full text |Cite
|
Sign up to set email alerts
|

Game formulations for structural optimization under uncertainty

Abstract: Summary We consider structural optimization (SO) under uncertainty formulated as a mathematical game between two players –– a “designer” and “nature”. The first player wants to design a structure that performs optimally, whereas the second player tries to find the worst possible conditions to impose on the structure. Several solution concepts exist for such games, including Stackelberg and Nash equilibria and Pareto optima. Pareto optimality is shown not to be a useful solution concept. Stackelberg and Nash ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…Holmberg et al [27] proposed a game theory approach to solve the worst-case-oriented stress constraints problems considering variation in the load direction; however, because the problems are non-convex, the existence of Nash equilibrium to the game problem proposed by Holmberg et al [27] is not guaranteed, and they rely on empirical observation of the numerical results. In the subsequent work, Thore et al [28] modelled the problem as a Stackelberg game, instead of a zero-sum game, and showed that, with this interpretation, it is possible to guarantee the existence of a solution to the problem. However, the numerical methodology to solve the Stackelberg game problem can be computationally inefficient.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Holmberg et al [27] proposed a game theory approach to solve the worst-case-oriented stress constraints problems considering variation in the load direction; however, because the problems are non-convex, the existence of Nash equilibrium to the game problem proposed by Holmberg et al [27] is not guaranteed, and they rely on empirical observation of the numerical results. In the subsequent work, Thore et al [28] modelled the problem as a Stackelberg game, instead of a zero-sum game, and showed that, with this interpretation, it is possible to guarantee the existence of a solution to the problem. However, the numerical methodology to solve the Stackelberg game problem can be computationally inefficient.…”
Section: Related Workmentioning
confidence: 99%
“…In the subsequent work, Thore et al. [28] modelled the problem as a Stackelberg game, instead of a zero-sum game, and showed that, with this interpretation, it is possible to guarantee the existence of a solution to the problem. However, the numerical methodology to solve the Stackelberg game problem can be computationally inefficient.…”
Section: Related Workmentioning
confidence: 99%
“…Our design problem is a mathematical game [5, 20, 57] between two players, each seeking to minimize an objective directly associated with either flow or temperature by controlling the design.…”
Section: The Design Problemmentioning
confidence: 99%
“…Our design problem is a mathematical game [5,20,57] between two players, each seeking to minimize an objective directly associated with either flow or temperature by controlling the design. The objective of the first player is to minimize the fluid compliance, which since we have no nonzero prescribed velocities amounts to minimizing…”
Section: The Design Problemmentioning
confidence: 99%
“…Bucher (2018) discussed strategies to have a suitable response surface model, evaluating its quality prediction, and discerning about important and unimportant variables. Thore et al (2019) proposed a topology structural optimization with uncertainty consideration, comparing three solution concepts: Pareto optima, Stackelberg equilibria, and Nash equilibria. Zhao et al (2020) introduced a novel approach based on the graph theory and the set theory aiming at controlling the number and size of interior holes of the structures.…”
Section: Optimizationmentioning
confidence: 99%